La socialisation au féminisme des étudiant·es par les médias après #MeToo - Albenga, Viviane (Politiques de communication, 2021)
La socialisation au féminisme par les médias est un sujet dont l’acuité se renforce depuis le hashtag MeToo. Dans ce contexte, nous montrerons comment certains médias ont pu participer à la socialisation politique au féminisme d’étudiant·es. En replaçant ces effets socialisateurs par rapport aux socialisations familiales et nationales et à l’expérience des violences sexistes, l’article met en évidence que certains médias ont pu agir comme un processus de transformation de dispositions incorporées en dispositions politique. Nous analyserons ensuite les usages politiques de médias en termes de participation et d’information : d’une part, les usages des comptes Instagram féministes ; d’autre part, les effets de la combinaison d’informations politiques généralistes par les réseaux sociaux et Internet aussi bien que la radio et la télévision. Ce dernier usage diversifié est le fait d’étudiant·es avec un capital culturel plus élevé qui se réfèrent davantage à l’histoire du mouvement féministe et de sa production théorique.
Keywords: #metoo; 2000 à aujourd'hui; 2010-2019; 2020-2029; approches et analyses; cours; cyberféminisme; discipline; europe; france; féminisme pop; militance; pol4102; premier cycle; périodes historiques; régions géographiques; réseaux sociaux; sciences humaines; socialisation; sociologie; thématiques

How far the ecowarrior will go: An ecofeminist reading of disney's Moana - Hernawati, Mala (3L: Language, Linguistics, Literature, 2021)
This article attempts to look into the fictional narrativization of women's significant and distinctive relationship with nature in Disney's Moana. Emphasizing the power and the unity of women and nature in Polynesian indigenous culture, Moana suggests that the destruction of nature results from exploitative and manipulative masculinity. Through ecofeminist perspectives, this essay observes that Moana offers critical views and promotes awareness of gender and environmental issues. These ideas are communicated through the visual and verbal depiction of power relations that defy patriarchal tradition alongside the expressions of protest against devaluation and abuse of nature and women. To put it in the context of the development of themes in Disney's princess line, Moana's presence can be a novel alternative to the typical images of women, namely a new portrayal of a female character whose primary concern is not romance but instead the sustainability of the environment where she lives. This study also confirms that Disney's animated princess films continuously adjust with the dynamics of global feminist discourse. © 2021 Penerbit Universiti Kebangsaan Malaysia. All rights reserved.
Keywords: 2000 à aujourd'hui; 2010-2019; approches et analyses; capitalisme; environnement; film d'animation; féminisme pop; histoire et politique; patriarcat; princesse disney; projet charge mentale; périodes historiques; systèmes d'oppressions; thématiques; écoféminisme

Comment l'impératif écologique aliène les femmes - Bouazzouni, Nora (Slate.fr, 2019)
Qu'elles soient du Sud ou du Nord, les femmes subissent le changement climatique ou les injonctions qui en découlent. C'est à se demander si féminisme et écologie sont compatibles.
Section: Égalités
Keywords: 2000 à aujourd'hui; 2010-2019; approches et analyses; care; com5170; communication; cours; discipline; environnement; féminisme pop; journalisme; premier cycle; périodes historiques; thématiques; écoféminisme; écologie

Navigating, challenging, and contesting normative gendered discourses surrounding women’s pornography use - Marques, Olga (Journal of Gender Studies, 2019)
While there exists some empirical research on women’s use of pornography, the manner in which women do, and how they understand their pornographic spectatorship, remains under-examined. Focusing on the narratives of 26 women gained through both focus groups and individual interviews, this research explores how women who use pornography and other sexually explicit materials navigate, reaffirm, challenge, and contest normative gendered boundaries that surround women’s sexuality, sexual pleasure, and women’s pornographic use. While ‘pornography as female degradation’ is the most visible feminist discourse, the findings of this study suggest that the meanings attributed to both the experience of engaging with pornography, as well as with pornographic materials themselves, were far from wholly degrading, and in fact, served to provide pleasure, sexual self-actualization, and even corporeal validation – disrupting normative discourses of desiring and desirable bodies.
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; canada; corps; cours; féminisme pop; ontario; premier cycle; périodes historiques; régions géographiques; sex1911; sexualité; thématiques

Trente - Darsigny, Marie (Les éditions du remue-ménage, 2018)
Trente, un nombre qui n’arrivera jamais et s’il arrive, je l’éviterai, comme j’ai une fois évité un chevreuil en conduisant sur la route, le chevreuil courait devant mon auto, à gauche il y avait la rivière et à droite il y avait le fossé, c’est beau la Montérégie, au lieu de choisir l’un ou l’autre il continuait d’avancer droit devant, puis il a fini par bondir vers le fossé. Moi j’aurais choisi l’eau et d’ailleurs, à chaque fois que j’empruntais ce chemin-là, ça me chicotait de savoir que juste un petit coup de volant pouvait m’envoyer dans la rivière, un jour on est en vie et un jour on ne l’est plus, c’est tout.
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; corps; cours; discours dominant; fem3500; féminisme pop; premier cycle; périodes historiques; québec; régions géographiques; santé; sexisme; systèmes d'oppressions; thématiques; violences

You play the girl: on Playboy bunnies, Stepford wives, train wrecks, and other mixed messages - Chocano, Carina (Houghton Mifflin Harcourt, 2017)
"Who is "the girl"? Look to movies, TV shows, magazines, and ads and the message is both clear and not: she is a sexed-up sidekick, a princess waiting to be saved, a morally infallible angel with no opinions of her own. She's whatever the hero needs her to be in order to become himself. She's an abstraction, an ideal, a standard, a mercurial phantom. In You Play the Girl, Chocano blends formative personal stories with insightful and emotionally powerful analysis. Moving from Bugs Bunny to Playboy Bunnies, Flashdance to Frozen, the progressive '70s through the backlash '80s, the glib '90s, and the pornified aughts–and at stops in between–she explains how growing up in the shadow of "the girl" taught her to think about herself and the world and what it means to raise a daughter in the face of these contorted reflections. In the tradition of Roxane Gay, Rebecca Solnit, and Susan Sontag, Chocano brilliantly shows that our identities are more fluid than we think, and certainly more complex than anything we see on any kind of screen."–Page 4 of cover.
Section: xxvi, 275 pages : illustration ; 21 cm
Keywords: 1900-1999; 1940-1949; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; com5170; communication; cours; discipline; discours dominant; féminisme pop; histoire et politique; journalisme; premier cycle; périodes historiques; représentation des femme*; sofia; systèmes d'oppressions; thématiques

The mask you live in (Kanopy Streaming, 2015)
HE MASK YOU LIVE IN follows boys and young men as they struggle to stay true to themselves while negotiating America’s narrow definition of masculinity. Pressured by the media, their peer group, and even the adults in their lives, our protagonists confront messages encouraging them to disconnect from their emotions, devalue authentic friendships, objectify and degrade women, and resolve conflicts through violence. These gender stereotypes interconnect with race, class, and circumstance, creating a maze of identity issues boys and young men must navigate to become “real” men. Experts in neuroscience, psychology, sociology, sports, education, and media also weigh in, offering empirical evidence of the “boy crisis” and tactics to combat it. The Mask You Live In ultimately illustrates how we, as a society, can raise a healthier generation of boys and young men.
Place: San Francisco, California, USA
Keywords: 1900-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; amériques; approches et analyses; care; cinéma; communication; cours; discipline; documentaire; féminisme pop; histoire et politique; intersectionnalité; masculinité; premier cycle; périodes historiques; représentation des hommes; régions géographiques; sex2283; sexualité; thématiques; travail; violences; états-unis

Femmes, attitudes performatives: aux lisières de la performance et de la danse - Colloque "Femmes, aux lisières de la performance et de la danse" (2012 : Vandœuvre-lès-Nancy, France), attitudes performatives; Boulbès, Carole; Centre culturel André Malraux de Vandœuvre-lès-Nancy; Boulbès, Carole; Centre culturel André Malraux de Vandœuvre-lès-Nancy (Les Presses du réel, 2014)
La place et le rôle des femmes dans l'art et dans le spectacle vivant, entre 1912 et 2012, aux lisières de la performance et de la danse. A l'heure des re-enactements et autres remakes des performances historiques, il semblait important de s'interroger sur la place des femmes dans les avant-gardes des années 1910-1970. Quel regard portons-nous, aujourd'hui, sur les pionnières qui ont profondément modifié la danse et la performance, en Europe et aux Etats-Unis ? Réunis pour la première fois, des historiens, des philosophes, des danseurs et deux chorégraphes ont accepté de faire le point sur leurs recherches. Par-delà les catégories artistiques (danse, performance, action, pantomime, théâtre, music-hall...) et les clivages (théorie / pratique ; forme / fond), ce livre est une invitation à partager leurs questionnements sur le spectacle vivant « au féminin », ses archives et ses références. Femmes, attitudes performatives rassemble dix contributions, une « interview performative » de La Ribot et un entretien sur La Part du rite de Latifa Laâbissi et Isabelle Launay.
Keywords: 1900-1909; 1900-1999; 1910-1919; 1920-1929; 1930-1939; 1940-1949; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; amériques; approches et analyses; artistes féministes; arts; corps; cours; danse; discipline; europe; femmes* artistes; féminisme pop; har4600; histoire de l'art; histoire de la danse; performance; premier cycle; périodes historiques; régions géographiques; sexualité; thématiques; états-unis

Femmes et médias: une image partiale et partielle - Bamberger, Clara (L'Harmattan, 2012)
Les femmes sont beaucoup moins visibles que les hommes dans les médias d'information. Les femmes, lorsqu'elles sont interviewées, le sont principalement en qualité de mères, de simples témoins ou de victimes. Sur la scène médiatique, les rôles de l'expert, de l'intellectuel ou du professionnel reste largement préemptés par les hommes. D'où vient cette représentation biaisée des sexes ?
Section: 1 vol. (91 p.) : graph., couv. ill. en coul. ; 22 cm.
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; com5170; communication; cours; discipline; discours dominant; europe; france; féminisme pop; histoire et politique; journalisme; premier cycle; périodes historiques; rapports sociaux de sexe; représentation des femme*; régions géographiques; systèmes d'oppressions; thématiques

Miss representation (Girls Club Entertainment, 2011)
Like drawing back a curtain to let bright light stream in, MISS REPRESENTATION uncovers a glaring reality we live with every day but fail to see. Written and directed by Jennifer Siebel Newsom, the film exposes how mainstream media contributes to the under-representation of women in positions of power and influence in America. The film challenges the media’s limited and often disparaging portrayals of women and girls, which make it difficult for women to achieve leadership positions and for the average woman to feel powerful herself. In a society where media is the most persuasive force shaping cultural norms, the collective message that our young women and men overwhelmingly receive is that a woman’s value and power lie in her youth, beauty, and sexuality, and not in her capacity as a leader. While women have made great strides in leadership over the past few decades, the United States is still 90th in the world for women in national legislatures, women hold only 3% of clout positions in mainstream media, and 65% of women and girls have disordered eating behaviors.
Place: San Francisco, Calif.
Keywords: 1900-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; amériques; approches et analyses; cinéma; communication; corps; cours; discipline; documentaire; féminisme pop; premier cycle; périodes historiques; représentation des femme*; régions géographiques; santé; sex2283; sexualité; thématiques; travail; états-unis

La transidentité: de l'espace médiatique à l'espace public - Espineira, Karine (L'Harmattan, 2008)
C'est à partir de l'opération de Christine Jorgensen en 1952 au Danemark, que le fait qu'un homme puisse devenir une femme, après une intervention chirurgicale, entre dans l'esprit du grand public en raison de sa très forte médiatisation. Les identités trans' sont alors loin de s'affirmer comme telles. Il faudra attendre la fin des années 80 pour assister à l'émergence d'une visibilité prenant une forme revendicative. Entre les deux, la psychiatrisation de l'identité. Grâce à l'Internet, les transidentités ne sont plus isolées les unes des autres et ne rejouent plus la dramatique du changement de sexe comme une individuelle et éternelle première fois. Une mémoire s'élabore, se fixe et génère une culture. Leurs relations à l'information et l'identitaire questionnent tout autant. Cette recherche considère le groupe transidentitaire comme un monde social s'institutionnalisant dans un esprit multidisciplinaire à la lumière des sciences de l'information et de la communication, de la psychosociologie, de la théorie de l'engagement, de l'ethnométhodologie, de la sociologie de la traduction et de la communication instituante. L'analyse du traitement télévisuel de la transidentité, considérée comme expression la plus singulière de l'identité, est-elle susceptible de donner des outils de lectures sur la construction des normes de genre au-delà de la transidentité ?
Section: 1 v. (187 p.) : couv. illustrations en coul. ; 22 cm
Keywords: 1900-1999; 1950-1959; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; approches et analyses; cours; danemark; discipline; discours dominant; europe; féminisme pop; identités LGBTQIA2+; premier cycle; périodes historiques; queer; régions géographiques; sexualité; shm4000; systèmes d'oppressions; thématiques; transféminisme

Radical gestures: feminism and performance art in North America - Wark, Jayne (McGill-Queen's University Press, 2006)
Wark brings together a wide range of artists, including Lisa Steele, Martha Rosler, Lynda Benglis, Gillian Collyer, Margaret Dragu, and Sylvie Tourangeau, and provides detailed readings and viewings of individual pieces, many of which have not been studied in detail before. She reassesses assumptions about the generational and thematic characteristics of feminist art, placing feminist performance within the wider context of minimalism, conceptualism, land art, and happenings
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; amérique du nord; amériques; approches et analyses; art contemporain; art féministe; arts; corps; cours; discipline; femmes* artistes; féminisme pop; har4600; histoire de l'art; histoire et politique; militance; performance; premier cycle; périodes historiques; régions géographiques; thématiques

La chirurgie mammaire et l'esthétiquement correct : le sein et les médias - Le Louarn, S.; Le Louarn, C. (Annales de Chirurgie Plastique Esthétique, 2005)
Résumé Cet article discute en quoi les normes du sein esthétiquement correct, les caractéristiques physiologiques du sein, l'allongement de la durée de vie et les possibilités de la chirurgie esthétique influencent la demande de modification mammaire. Puis il examine comment le sujet des modifications mammaires est traité dans différents médias : presse écrite (notamment féminine), documentaires et spectacles de téléréalité. Il constate un paradoxe entre d'une part, un contexte social qui durcit des normes, encourage la quête du bien-être et la réalisation de soi et prône la tolérance et, d'autre part, la réalité d'un certain déni du droit des femmes à choisir leur apparence mammaire. L'article tente de décrypter les obstacles historiques, philosophiques, sociaux, religieux et idéologiques impliqués. Enfin, il propose une nouvelle grille de lecture du positionnement d'un individu par rapport à la chirurgie esthétique selon deux axes : le « Faire » et le « Dire ». Cette grille pourra aider le chirurgien plasticien à mieux décoder la demande de chaque patiente, pour mieux la satisfaire.
Number: 5
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; approches et analyses; corps; corps féminin; cours; discipline; discours médiatique; esthétique; europe; france; féminisme pop; hétérosexisme; occident; premier cycle; périodes historiques; régions géographiques; santé; sciences humaines; soc2051; sociologie; systèmes d'oppressions; thématiques

Pornography, Women and Feminism: Between Pleasure and Politics - Ciclitira, Karen (Sexualities, 2004)
This article draws on a qualitative research study which set out to explore women’s experiences and views of pornography within the broader context of conflicting feminist positions on pornography. The research methodology posed an implicit criticism of the kind of ‘findings’ familiar from mainstream psychological research: semi-structured interviews were conducted with women from diverse backgrounds in the UK, and feminist theory and discourse analysis were used to inform interpretation of their accounts. Although the question of feminism was not explicitly raised by the interviewer, it emerged as a recurrent theme in interviews, with interviewees suggesting that the feminist anti-porn stance in particular has influenced their perspective on pornography. Their accounts show that women’s experiences are variegated, individual and complex, and that discourses of pornography and feminism may be negotiated in unpredictable ways.
Keywords: 2000 à aujourd'hui; 2000-2009; approches et analyses; cours; discipline; europe; féminisme pop; pornographie; premier cycle; psychologie; périodes historiques; recherche qualitative; ressource en ligne; royaume-uni; régions géographiques; sciences humaines; sex1911; sexualité; thématiques

Catching a wave: reclaiming feminism for the 21st century - Dicker, Rory Cooke; Piepmeier, Alison (Northeastern University Press, 2003)
Young women today have benefited from the strides made by grassroots social activists in the 1960s and 1970s, yet they are hesitant to identify themselves as feminists and seem apathetic about carrying the torch of older generations to redress persistent sexism and gender-based barriers. Contesting the notion that we are in a post-feminist age, this collection of essays identifies a third wave of feminism. The contributors argue that the next generation needs to develop a politicized, collective feminism that both builds on the strategies of second wave feminists and is grounded in the material realities and culture of the 21st century. Organized into five sections which mirror the stages of consciousness-raising, the book looks at a broad range of perspectives on the diversity, complexity, multiplicity and playfulness of the third wave. It is also a call to action for new voices to redefine a feminism that is not only personally aware, but also politically involved. (source: Nielsen Book Data)
Section: x, 338 p. ; 24 cm Table des matières Introduction / Rory Dicker and Alison Piepmeier The "big lie": false feminist death syndrome, profit, and the media / Jennifer L. Pozner In a word, Baywatch / Susannah B. Mintz. Reviving Lolita ; or, because junior high is still hell / Alyssa Harad "That's not fair!" : nurturing girls' natural feminism / Nancy Gruver Voices and visions : a mother and daughter discuss coming to feminism and being feminist / Roxanne Harde and Erin Harde Please–stop thinking about tomorrow : building a feminist movement on college campuses for today / Sarah Boonin Who's the next Gloria? : the quest for the third wave superleader / Jennifer Baumgardner and Amy Richards Buffy the vampire slayer : the next generation of television / Michele Byers Third World, third wave feminism(s) : the evolution of Arab American feminism / Susan Muaddi Darraj Feminism's family problem : feminist generations and the mother-daughter trope / Astrid Henry Do the ladies run this– ? Some thoughts on hip-hop feminism / Gwendolyn D. Pough The transfeminist manifesto / Emi Koyama Hearing the daughter voice : The Bat Kol as Rrrabbi Grrrl / Alana Suskin Rocking the gender order / Mimi Schippers Pranks and fake porn : doing feminism my way / Kristina Sheryl Wong Afterword / Katha Pollitt and Jennifer Baumgardner.
Keywords: 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; approches et analyses; cours; féminisme pop; militance; premier cycle; périodes historiques; soc2014; thématiques; transféminisme; troisième vague

"You Can Never Be Too Rich or Too Thin": Popular and Consumer Culture and the Americanization of Asian American Girls and Young Women - Lee, Stacey J.; Vaught, Sabina (The Journal of Negro Education, 2003)
First- and second-generation youth of color are vulnerable to racialized images of gender and sexuality as reflected in and perpetuated by dominant forms of popular and consumer cultures. These popular images inform the process of Americanization, including racialized sexualization, for first- and second-generation Americans. This paper examines the way first- and second-generation Asian American girls and young women interpret and reinterpret popular representations of their positions in the United States. Data from two qualitative studies on Asian American young women will be presented.
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; asie; corps; cours; discipline; féminisme pop; hmong; intersectionnalité; laos; premier cycle; périodes historiques; racisme; représentation des femme*; représentation des femmes* racisées; ressource en ligne; régions géographiques; sciences de l'éducation; sex2283; sexisme; systèmes d'oppressions; thématiques; états-unis